Non-occlusive mesenteric ischemia in critically ill patients: does bedside laparoscopy offer any real benefit? - Mirko Barone; Regina Frontera; Rita Vaia Liouras; Massimo Ippoliti; Luca Serano; Carmine Giovanni Iovino; Ivan Dell’Atti; Luigi Vetrugno; Felice Mucilli; Salvatore Maurizio Maggiore (Emergency and Critical Care Medicine)
Abstract. Non-occlusive mesenteric ischemia in critically ill patients still has a poor prognosis. Despite several established risk factors, the interaction between clinical conditions and perfusion mismatch often leads to progressive organ failure. Workup is challenging because of the absence of typical abdominal signs and symptoms due to sedation, poor reactivity, need for ventilation, and confounding comorbidities. Moreover, imaging has poor specificity with findings often inconclusive. A bedside exploratory laparoscopy, as a complementary strategy, would allow for early and prompt diagnosis. Limits of a minimally invasive surgical rationale lie upon the effects of pneumoperitoneum induction, surgical stress, logistical resources, expertise, and costs.